(untitled) - Moreton, Bethany (Cambridge, Mass, 2009)
This extraordinary biography of Wal-Mart's world shows how a Christian pro-business movement grew from the bottom up as well as the top down, bolstering an economic vision that sanctifies corporate globalization
Keywords: Thương mại,Business; Khía cạnh tôn giáo,Religious aspects